Replenishing effect of dehyroepiandrosteron on the ovary toxicity induced by exposure to vinylcyclohexene diepoxide in mature female rats (Albayan Scientific Journal, 2023)
Administrations of dehydroepiandrosterone (DHEA) to female had effects on ovarian response ovarian reserve, oocytes embryo yield quality, cumulus pregnancy rate, live birth rate and also improved the miscarriage rate and improve the results of infertility treatment. The aim of present study is to examine the replenishing effect of dehyroepiandrosteron (DHEA) on the reprotoxicity induced by exposure to vinylcyclohexene diepoxide (VCD) on mature female rats. 48 mature female rats were divided into equal four groups. The control group was injected intraperitoneally with sesame oil (0.2 ml) daily for 45 days. The second group was injected with DHEA (0.2 ml) once daily for 45 days. The third group was injected with VCD (1.2 ml) once daily for 45 days. The fourth group was injected with DHEA (0.2 ml) +VCD (1.2 ml) once daily for 45 days. Results showed that the DHEA treated females was close to the control rats in most of the measured plasma hormone levels, except DHEA and CORT hormones. While the group treated with VCD recorded a significant decrease (P
Keywords: Dehydroepiandrosterone; Vinylcyclohexene diepoxide; Reproductive system; Sexual hormones; Female rat.